Detection of cell proliferation in adults of the water bear Hypsibius dujardini (Tardigrada) via incorporation of a thymidine analog. (April 2018) - Gross, V.; Bährle, R.; Mayer, G.
Graphical abstract: Highlights: Cells of the midgut are continuously renewed in tardigrades. Cells arise from proliferation zones in the anterior and posterior of the midgut. Approximately one week is required to replace all cells of the midgut. Abstract: The taxon Tardigrada, commonly called "water bears", consists of microscopic, eight-legged invertebrates that are well known for their ability to tolerate extreme environmental conditions. Their miniscule body size means that tardigrades possess a small total number of cells, the number and arrangement of which may be highly conserved in some organs. Although mitoses have been observed in several organs, the rate and pattern of cell divisions in adult tardigrades has never been characterized. In this study, we incubated live tardigrades over a period of several days with a thymidine analog in order to visualize all cells that had divided during this time. We focus on the midgut, the largest part of the digestive system. Our results show that new cells in the midgut arise from the anterior and posterior ends of this organ and either migrate or divide toward its middle. These cells divide at a constant rate and all cells of the midgut epithelium are replaced in approximately one week. On the other hand, we found no cell divisions in the nervous system or any other major organs, suggesting that the cell turnover of these organs may be extremely slow or dependent on changing environmental conditions.